Substituted isatin aromatic hydrocarbon copolymer, preparation method and polymer anion exchange membrane

By using copolymerization reaction technology of biaryl compounds, substituted isatin and azacyclone in the polymer anion exchange membrane, a substituted isatin aromatic copolymer was formed, and a quaternized polymer was formed by methylation of iodomethyl ionized, the existing membranes were solved, and anion exchange membrane with high conductivity, mechanical strength and chemical stability were achieved.

CN119552328APending Publication Date: 2025-03-04BEI JING ZHI QING KE JI YOU XIAN GONG SI

Patent Information

Application Number
CN202411870042.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing polymer anion exchange membranes have problems such as insufficient alkali resistance, low electrical conductivity and poor mechanical stability in alkaline environments.

Method used

The aromatic structure of biaryl compounds is used as the backbone, and the indigo is replaced as the hydrophobic regulation unit and the ion transport channel optimization unit, and the azacyclone is used as the cation center. The continuous polycondensation reaction is carried out under acid catalytic conditions to form a substituted indigo aromatic copolymer, and a quaternized polymer is formed through methyl iodomethyl methylation reaction to prepare a polymer anion exchange membrane.

Benefits of technology

The alkali stability, conductivity and mechanical properties of the polymer anion exchange membrane are significantly improved, forming a class of anion exchange membranes with excellent comprehensive performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119552328A_ABST
    Figure CN119552328A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of high polymer materials, and particularly relates to a substituted isatin aromatic hydrocarbon copolymer, a preparation method and a polymer anion exchange membrane. The aromatic structure of a biaryl compound is used as a main chain, substituted isatin is used as a hydrophobic structure, azacyclo-ketone is used as a cation center, and the aryl of the biaryl compound and the carbonyl of the substituted isatin or the carbonyl of the azacyclo-ketone are reacted under the catalytic action of acid, so that the aromatic structure of the biaryl compound is obtained. And carrying out continuous polycondensation reaction to form the substituted isatin aromatic hydrocarbon copolymer. The preparation method comprises the following steps: carrying out methylation reaction on a substituted isatin aromatic hydrocarbon copolymer to form a quaternized polymer; the quaternized polymer is used as a raw material to prepare the polymer anion exchange membrane. The polymer anion exchange membrane prepared by the invention has the characteristics of no ether bond, high mechanical strength, high conductivity and high chemical stability, and is an anion exchange membrane with excellent comprehensive performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a substituted isatin aromatic copolymer and a preparation method thereof, and a polymer anion exchange membrane. Background Art

[0002] Hydrogen is a promising alternative energy source that can replace fossil fuels and alleviate environmental problems. However, most hydrogen is produced by burning fossil fuels, called grey hydrogen, and the production of grey hydrogen emits a large amount of carbon dioxide. Water electrolysis technology has been developed as a sustainable technology for producing high-purity hydrogen, and the hydrogen produced by this method is called green hydrogen.

[0003] Traditional alkaline electrolyzers immerse two electrodes in an aqueous liquid electrolyte, which is usually 30wt% to 40wt% potassium hydroxide. Its main advantage is that it can use cheap non-platinum noble metal catalysts to reduce the cost of alkaline water electrolysis hydrogen production equipment. However, the electrolyte concentration in alkaline water electrolysis hydrogen production is too high, and the porous diaphragm in the electrolyzer cannot effectively separate the hydrogen produced by the cathode and the oxygen produced by the anode, thereby reducing the efficiency of the electrolyzer.

[0004] Existing technologies develop polymer electrolyte membranes to replace porous diaphragms, taking advantage of the compactness and excellent gas barrier capabilities of polymer electrolyte membranes. Compared with traditional alkaline electrolyzers, polymer electrolyte membranes can improve gas purity and reduce the volume of electrolyzers. Polymer electrolyte membranes include proton exchange membranes and anion exchange membranes. Proton exchange membranes use perfluorosulfonic acid membranes, which are expensive. Their working environment is strongly acidic and requires acid-resistant precious metal catalysts such as platinum and iridium, and acid-resistant bipolar plates. The overall cost is at least twice as expensive as anion exchange membranes. In addition, my country's precious metals are all dependent on imports, which limits the application of proton exchange membranes. Anion exchange membranes are widely used in water electrolysis technology due to their low cost, lack of precious metal catalysts, and low gas permeability.

[0005] Anion exchange membrane is the core key material. Currently, most anion exchange membranes are modified from basic engineering plastic polymers such as polystyrene and polyetheretherketone. These materials lack efficient ion conduction channels in nature. The presence of polar bonds leads to poor stability of polymer chains in alkaline environments. Moreover, the strength of the modified polymers is greatly reduced, which cannot meet the requirements of their application in anion water electrolysis devices. Summary of the invention

[0006] In order to solve the technical problems of insufficient alkali resistance, low conductivity and poor mechanical stability of the anion exchange membrane prepared by the above polymer, the present invention provides a substituted indigo aromatic copolymer and a preparation method and a polymer anion exchange membrane. The present invention uses the aromatic structure of the biaryl compound as the main chain, and on the basis of retaining the aromatic structure of the main chain, uses the substituted indigo as the hydrophobicity adjustment unit and the ion transmission channel optimization unit, and uses the nitrogen heterocyclic ketone as the cationic center. Under the catalytic action of the acid, the carbonyl group of the substituted indigo or the carbonyl group of the nitrogen-containing heterocyclic ketone is protonated, and under the nucleophilic attack of the aromatic group, the C=O double bond of the carbonyl group is opened to become C-OH, and the hydroxyl group is protonated by the acid again, and the hydroxyl carbon is attacked by the aromatic group of another molecule, and the continuous polycondensation reaction is performed to form the substituted indigo aromatic copolymer.

[0007] The first object of the present invention is to provide a substituted isatin aromatic copolymer, the chemical structure of which is shown in Formula 1:

[0008]

[0009] Wherein, R1, R2, R3 and R4 are independently selected from one of methyl, alkyl, halogenated alkyl, H, F, Cl and Br substituents; R5 is H or a carbon straight chain alkyl with 1 to 12 carbon atoms; Ar is a biaryl compound; and B is an azacyclic ketone.

[0010] Preferably, the biaryl compound includes one or more of biphenyl, p-terphenyl, m-terphenyl, p-quaterphenyl, fluorene, carbazole, aminofluorene, dibenzothiophene, dibenzofuran, 1,1'-binaphthyl, 2,2'-dihydroxybiphenyl, 4,4'-dihydroxybiphenyl and S-naphthol.

[0011] Preferably, the azacyclic ketone includes one or more of 4-piperidone, 1-methyl-4-piperidone and 3-quinuclidinone.

[0012] The second object of the present invention is to provide a method for preparing the above-mentioned substituted isatin aromatic copolymer, characterized in that it comprises the following steps:

[0013] With the aromatic structure of the biaryl compound as the main chain, the substituted isatin as the hydrophobic structure and the nitrogen heterocyclic ketone as the cationic center, the biaryl compound, the substituted isatin and the nitrogen heterocyclic ketone are subjected to continuous condensation reaction under the catalytic action of an acid so as to form a substituted isatin aromatic copolymer.

[0014] It should be noted that the specific preparation process of the substituted isatin aromatic copolymer is as follows: dissolving the biaryl compound, substituted isatin and azacyclic ketone in a solvent in turn to obtain a reaction solution; in order to control the reaction rate of the reaction solution, adding trifluoroacetic acid to the reaction solution under a 0°C water bath, and then dripping trifluoromethanesulfonic acid to obtain a viscous solution; immersing the viscous solution in a potassium carbonate solution for many times so that the acid-protonated nitrogen on the nitrogen heterocycle is converted into a non-protonated nitrogen heterocycle through an acid-base reaction to obtain a solid polymer; washing and drying the solid polymer to obtain a substituted isatin aromatic copolymer. The role of potassium carbonate is to convert the acid-protonated nitrogen on the nitrogen heterocycle into a non-protonated nitrogen heterocycle through an acid-base reaction, which is beneficial to the quaternization of methyl iodide.

[0015] It should also be noted that, under the catalytic action of the acid, the carbonyl of the substituted isatin or the carbonyl of the nitrogen-containing heterocyclic ketone is protonated, and under the nucleophilic attack of the aromatic group, the C=O double bond of the carbonyl is opened and becomes C-OH, the hydroxyl group is protonated by the acid again, and the hydroxyl carbon is attacked by the aromatic group of another molecule, and the condensation reaction is continuous to form a substituted isatin aromatic copolymer. Therefore, the total amount of substituted isatin and azacyclic ketone and the amount ratio of the biaryl compound have a direct impact on the substituted isatin aromatic copolymer formed. The higher the molar ratio of the total mole of substituted isatin and azacyclic ketone to the biaryl compound, the shorter the polymerization time used, and a high-molecular-weight substituted isatin aromatic copolymer with a super large molecular weight can be obtained, but it is easy to cause the molecular weight distribution of the substituted isatin aromatic copolymer to be uneven, thereby reducing the overall strength of the substituted isatin aromatic copolymer; however, the lower the molar ratio of the total mole of substituted isatin and azacyclic ketone to the biaryl compound, the more uniform the molecular weight distribution of the substituted isatin aromatic copolymer is, and the longer the required reaction time is, so it is necessary to comprehensively consider and select a suitable ratio. Preferably, in the present invention, the molar ratio of the total mole of the substituted isatin and the azacyclic ketone to the biaryl compound is 1 to 2:1.

[0016] Preferably, the molar ratio of the substituted isatin to the azacyclic ketone is 1:0.01-99, and more preferably, the molar ratio of the substituted isatin to the azacyclic ketone is 1:5-10.

[0017] The concentration of the acid directly affects the molecular weight of the substituted isatin aromatic copolymer. The more acid, the higher the molecular weight of the substituted isatin aromatic copolymer. Preferably, the molar ratio of the biaryl compound to trifluoroacetic acid is 1:0.1 to 2.0. Preferably, the molar ratio of the biaryl compound to trifluoromethanesulfonic acid is 1:1 to 50.

[0018] Preferably, the substituted indigo includes one of 5-methyl indigo, 7-methyl indigo, 5-fluoro indigo, 6-fluoro indigo, 7-fluoro indigo, 5,6-difluoro indigo, 4,6-difluoro indigo, 5,7-difluoro indigo, 6-chloro indigo, 7-chloro indigo and 7-trifluoromethyl indigo.

[0019] Preferably, the solvent is one of dichloromethane, 1,2-dichloroethane and other halogenated hydrocarbon solvents. The solvent has good solubility to dissolve the biaryl compound, substituted isatin and azacyclic ketone.

[0020] Preferably, the stirring time of the present invention is 2 h to 100 h, and the reaction in the reaction solution is carried out in an orderly manner through stirring.

[0021] The third object of the present invention is to provide a polymer anion exchange membrane prepared from the above-mentioned substituted isatin aromatic copolymer.

[0022] The present invention forms a quaternary ammonium polymer by methylating the nitrogen heterocyclic group in the substituted isatin aromatic copolymer with methyl iodide, and uses the quaternary ammonium polymer as a polymer raw material to prepare a polymer anion exchange membrane. The preparation method of the present invention is simple to operate, not only effectively enhances the conductivity of the polymer anion exchange membrane, but also effectively limits the swelling of the polymer chain, and significantly improves the alkali stability of the polymer anion exchange membrane.

[0023] Preferably, the polymer anion exchange membrane is prepared by the following steps:

[0024] Step 1, dissolving the substituted indigo carmine aromatic copolymer in a first solvent to obtain a first mixed solution; in a dark and closed environment, adding methyl iodide to the first mixed solution, stirring the reaction and then filtering under reduced pressure to obtain a filtrate, adding the filtrate to a precipitant, and reacting the nitrogen heterocyclic group in the indigo carmine aromatic copolymer with methyl iodide to form a quaternary ammonium polymer to obtain a quaternary ammonium polymer.

[0025] Preferably, the usage ratio of the isatin aromatic copolymer to the first solvent is 1.0 g: 5 ml to 30 ml.

[0026] Step 2: using a quaternary ammonium polymer as a raw material, dissolving the quaternary ammonium polymer in a second solvent to obtain a second mixed solution, casting the second mixed solution to obtain a substrate membrane, and exchanging hydroxide ions on the substrate membrane to obtain a polymer anion exchange membrane.

[0027] It should be noted that, in the present invention, methyl iodide is added to the first mixed solution to promote the reaction of methyl iodide with the substituted isatin aromatic copolymer. The entire reaction process needs to be carried out in a dark and closed environment to avoid the decomposition of methyl iodide by light, thereby promoting the methylation reaction of the nitrogen heterocyclic group in the substituted isatin aromatic copolymer with methyl iodide to form a quaternary ammonium polymer. Preferably, the amount ratio of the substituted isatin aromatic copolymer to methyl iodide is 1.0g:1ml~5ml.

[0028] Preferably, the first solvent and the second solvent are both one of dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide and N-methylpyrrolidone.

[0029] Preferably, the stirring time in step 1 is 24h to 36h, and the stirring temperature is 40°C to 50°C.

[0030] Preferably, the precipitant is one of diethyl ether, ethanol, methanol ethyl acetate, water, cyclohexane and n-hexane, which is used to precipitate the polymer in the filtrate.

[0031] In order to remove the impurities remaining in the polymer, the polymer was washed several times with ethanol and water, and the washed polymer was filtered and dried at 80° C. for 24 hours to remove the moisture and organic solvent of the washed polymer to obtain a quaternary ammonium polymer.

[0032] The usage ratio of the quaternary ammonium polymer to the second solvent is 0.4 g: 20 ml to 30 ml.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] The substituted indigo aromatic copolymer of the present invention improves the rigidity and stability of the substituted indigo aromatic copolymer skeleton through the aromatic structure of the biaryl compound, regulates the hydrophobicity of the polymer chain by replacing the fluorine-containing substituent in the indigo, uses azacycloketone as the cationic center of the substituted indigo aromatic copolymer, and under the joint action of the biaryl compound, the substituted indigo and azacycloketone, improves the structural strength, hydrophobicity and stability of the substituted indigo aromatic copolymer, thereby meeting the application requirements of the substituted indigo aromatic copolymer in anionic water electrolysis devices.

[0035] The present invention uses the aromatic structure of the biaryl compound as the main chain, the substituted isatin as the hydrophobic structure, and the nitrogen heterocyclic ketone as the cationic center. The biaryl compound, the substituted isatin and the nitrogen heterocyclic ketone are subjected to the catalytic action of an acid, the carbonyl group of the substituted isatin or the carbonyl group of the nitrogen-containing heterocyclic ketone is protonated, and under the nucleophilic attack of the aromatic group, the C=O double bond of the carbonyl group is opened to become C-OH, the hydroxyl group is protonated by the acid again, and the hydroxyl carbon is attacked by the aromatic group of another molecule, and a substituted isatin aromatic copolymer is formed through a continuous polycondensation reaction.

[0036] The present invention uses substituted indigo carmine aromatic copolymers to prepare polymer anion exchange membranes. The biaryl compound as the main chain provides excellent mechanical strength for the anion exchange membrane through a rigid benzene ring skeleton; the substituted indigo carmine regulates the hydrophobicity of the polymer chain through a fluorine-containing substituent to optimize the hydrophilicity and hydrophobicity of the polymer anion exchange membrane, optimizes the ion transmission channel from a microscopic perspective, improves the ion transmission efficiency, and effectively inhibits the swelling of the polymer anion exchange membrane. The nitrogen-containing heterocyclic compound forms a quaternized polymer after being modified by methyl iodide methylation, which can provide a highly stable cationic center and improve the chemical stability of the anion membrane.

[0037] The present invention replaces indigo carmine as a hydrophobicity regulating unit and an ion transmission channel optimizing unit, and its introduction improves the ion transmission efficiency, effectively inhibits the swelling of the membrane and improves the mechanical properties of the membrane; the nitrogen-containing heterocyclic compound forms a quaternary ammonium polymer through a methylation reaction, which significantly improves the ion conductivity and the chemical stability of the anion exchange membrane; the biaryl compound provides excellent mechanical strength for the anion exchange membrane by improving the rigidity and stability of the polymer skeleton. The polymer anion exchange membrane prepared by the present invention has the characteristics of no ether bond, high mechanical strength, high conductivity and high chemical stability, and is a type of anion exchange membrane with excellent comprehensive performance.

[0038] The polymer anion exchange membrane of the present invention is a flexible polymer electrolyte membrane used in the process of hydrogen production in a water electrolyzer. The polymer electrolyte membrane has both fixed ion groups in its structure and can obtain ion conductivity by absorbing liquid electrolytes, which also means that they have higher alkaline stability than anion exchange membranes. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 This is the hydrogen nuclear magnetic resonance spectrum of QAFuI-10a prepared in Example 1 of the present invention.

[0040] Figure 2 This is the hydrogen nuclear magnetic resonance spectrum of QAFuI-7b prepared in Example 2 of the present invention.

[0041] Figure 3 This is the hydrogen nuclear magnetic resonance spectrum of QAFuI-10c prepared in Example 3 of the present invention.

[0042] Figure 4 This is the mechanical strength of the QAFuI-10a exchange membrane prepared in Application Example 1 of the present invention in a wet state.

[0043] Figure 5 This is the mechanical strength of the QAFuI-7b exchange membrane prepared in Application Example 2 of the present invention in a wet state.

[0044] Figure 6 The ionic conductivity of QAFuI-10a prepared in Example 1 of the present invention at different temperatures.

[0045] Figure 7 The ion conductivity of the QAFuI-7b exchange membrane prepared in Example 2 of the present invention at different temperatures.

[0046] Figure 8 The swelling rate and water content data of QAFuI-10a prepared in Example 1 of the present invention at different temperatures.

[0047] Fig. 9The performance of QAFuI-7b prepared in Example 2 of the present invention in an alkaline anion exchange membrane water electrolysis device. DETAILED DESCRIPTION

[0048] In order to enable those skilled in the art to better understand the technical solution of the present invention and implement it, the present invention is further described below in conjunction with specific embodiments and drawings. In the description of the present invention, unless otherwise specified, the reagents used are all commercially available, and the methods used are all conventional techniques in the art.

[0049] It should be noted that the substituted isatin aromatic copolymer prepared in the present invention is denoted as AFuI-x, wherein x is the molar ratio of the aromatic structural unit in the biaryl compound to the substituted isatin.

[0050] Example 1

[0051] This embodiment provides a method for preparing a substituted isatin aromatic copolymer.

[0052] With the aromatic structure of the biaryl compound as the main chain, the substituted isatin as the hydrophobic structure and the nitrogen heterocyclic ketone as the cationic center, the biaryl compound, the substituted isatin and the nitrogen heterocyclic ketone are subjected to continuous condensation reaction under the catalytic action of an acid so as to form a substituted isatin aromatic copolymer.

[0053] 1.1) 7.83 g of p-terphenyl, 0.56 g of 5-fluoroindigo red and 3.85 g of N-methyl-4-piperidone were dissolved in 21.7 mL of dichloromethane to obtain a reaction solution.

[0054] 1.2) The reaction flask containing the reaction solution was immersed in an ice-water bath, 3.0 mL of trifluoroacetic acid was added at 0°C, and 24.4 mL of trifluoromethanesulfonic acid was added dropwise. After stirring at this temperature for 2 h, a dark brown viscous solution was obtained.

[0055] 1.3) Pour the viscous solution into 250 mL of potassium carbonate solution, soak for 12 h, break up the precipitate, filter and obtain a semi-solid polymer.

[0056] 1.4) The semi-solid polymer was immersed in potassium carbonate solution again and stirred at 45°C for 12 hours to obtain a brown-grey solid polymer.

[0057] 1.5) The polymer was washed with deionized water for several times until it was neutral, and dried at 80°C for 24 hours to obtain a substituted isatin aromatic copolymer, which was designated as AFuI-10a. The preparation reaction route is shown in Reaction Formula 1:

[0058]

[0059] The H NMR spectrum of AFuI-10a is as follows Figure 1 As shown, the data of nuclear magnetic hydrogen spectrum are as follows: 1 HNMR (400 MHz, DMSO-d6, ppm) δH=10.79, 7.71-6.89, 3.34, 3.26, 3.10, 2.89, 2.50, 2.00, indicating that the present invention successfully synthesized the substituted isatin aromatic copolymer.

[0060] Example 2

[0061] This embodiment provides a method for preparing a substituted isatin aromatic copolymer.

[0062] Synthesis of substituted inatin aromatic copolymers: With the aromatic structure of the biaryl compound as the main chain, the substituted inatin as the hydrophobic structure, and the nitrogen heterocyclic ketone as the cationic center, the biaryl compound, the substituted inatin and the nitrogen heterocyclic ketone are subjected to continuous condensation reaction under the catalysis of an acid, so that the carbonyl group of the substituted inatin or the carbonyl group of the nitrogen-containing heterocyclic ketone is attacked by the nucleophilic attack of the aromatic group of the biaryl compound, thereby forming a substituted inatin aromatic copolymer.

[0063] 1.1) 6.22 g of p-terphenyl, 0.346 g of 5,6-difluoroindigo red and 3.85 g of N-methyl-4-piperidone were dissolved in 16.5 mL of dichloromethane to obtain a reaction solution.

[0064] 1.2) The reaction flask containing the reaction solution was immersed in an ice-water bath, 2.6 mL of trifluoroacetic acid was added at 0°C, and 19.5 mL of trifluoromethanesulfonic acid was added dropwise. After stirring at this temperature for 2 h, a dark brown viscous solution was obtained.

[0065] 1.3) Pour the viscous solution into 250 mL of potassium carbonate solution, soak for 12 h, break up the precipitate, filter and obtain a semi-solid polymer.

[0066] 1.4) The semi-solid polymer was immersed in potassium carbonate solution again for 12 hours to obtain a brown-grey solid polymer.

[0067] 1.5) The polymer was washed with deionized water for several times until it was neutral, and dried at 80°C for 24 hours to obtain a substituted isatin aromatic copolymer, which was designated as AFuI-7b. The preparation reaction route is shown in Reaction Formula 2:

[0068]

[0069] The H NMR spectrum of AFuI-7b is as follows Figure 2 As shown, the data of nuclear magnetic hydrogen spectrum are as follows: 1HNMR (400 MHz, DMSO-d6, ppm) δH=11.0, 7.71-7.00, 3.60, 3.34, 3.10, 2.89, 2.50, 2.00, indicating that the present invention successfully synthesized the substituted isatin aromatic copolymer.

[0070] The difference between this embodiment and embodiment 1 is that the indigo red is replaced with 5,6-fluoroindigo red.

[0071] Example 3

[0072] This embodiment provides a method for preparing a substituted isatin aromatic copolymer.

[0073] Synthesis of substituted isatin aromatic copolymers: Using the aromatic structure of the biaryl compound as the main chain, the substituted isatin as the hydrophobic structure, and the nitrogen heterocyclic ketone as the cationic center, the biaryl compound, the substituted isatin and the nitrogen heterocyclic ketone are subjected to continuous condensation reaction under the catalysis of an acid so as to form a substituted isatin aromatic copolymer.

[0074] 1.1) 6.22 g of p-terphenyl, 0.44 g of 5-methylisatin and 3.06 g of N-methyl-4-piperidone were dissolved in 17.9 mL of dichloromethane to obtain a reaction solution.

[0075] 1.2) The reaction flask containing the reaction solution was immersed in an ice-water bath, 2.4 mL of trifluoroacetic acid was added at 0°C, and 19.4 mL of trifluoromethanesulfonic acid was added dropwise. After stirring at this temperature for 2 h, a dark brown viscous solution was obtained.

[0076] 1.3) Pour the viscous solution into 250 mL of potassium carbonate solution, soak for 12 h, break up the precipitate, filter and obtain a semi-solid polymer.

[0077] 1.4) The semi-solid polymer was immersed in potassium carbonate solution again for 12 hours to obtain a brown-grey solid polymer.

[0078] 1.5) The polymer was washed with deionized water for several times until it was neutral, and dried at 80°C for 24 hours to obtain a substituted isatin aromatic copolymer, which was designated as AFuI-10c. The preparation reaction route is shown in Reaction Formula 3:

[0079]

[0080] The H NMR spectrum of AFuI-10c is as follows Figure 3 As shown, the data of nuclear magnetic hydrogen spectrum are as follows: 1HNMR (400 MHz, DMSO-d6, ppm) δH=10.79, 7.73-6.90, 3.65, 3.34, 3.26, 3.10, 2.89, 2.50, 2.00, indicating that the present invention successfully synthesized the substituted isatin aromatic copolymer.

[0081] The difference between this embodiment and embodiment 1 is that the isatin is replaced by 5-methylisatin.

[0082] Example 4

[0083] This embodiment provides a method for preparing a substituted isatin aromatic copolymer.

[0084] With the aromatic structure of the biaryl compound as the main chain, the substituted isatin as the hydrophobic structure and the nitrogen heterocyclic ketone as the cationic center, the biaryl compound, the substituted isatin and the nitrogen heterocyclic ketone are subjected to continuous condensation reaction under the catalytic action of an acid so as to form a substituted isatin aromatic copolymer.

[0085] 1.1) 7.83 g of p-terphenyl, 2.8 g of 5-fluoroindigo red and 1.925 g of 1-methyl-4-piperidone were dissolved in 21.7 mL of dichloromethane to obtain a reaction solution.

[0086] 1.2) The reaction flask containing the reaction solution was immersed in an ice-water bath, 3.0 mL of trifluoroacetic acid was added at 0°C, and 24.4 mL of trifluoromethanesulfonic acid was added dropwise. After stirring at this temperature for 2 h, a dark brown viscous solution was obtained.

[0087] 1.3) Pour the viscous solution into 250 mL of potassium carbonate solution, soak for 16 h, break up the precipitate, filter and obtain a semi-solid polymer.

[0088] 1.4) The semi-solid polymer was immersed in potassium carbonate solution again and stirred at 45°C for 16 hours to obtain a brown-grey solid polymer.

[0089] 1.5) The polymer was washed with deionized water for several times until it became neutral, and dried at 80° C. for 24 h to obtain a substituted isatin aromatic copolymer.

[0090] Example 5

[0091] This embodiment provides a method for preparing a substituted isatin aromatic copolymer.

[0092] With the aromatic structure of the biaryl compound as the main chain, the substituted isatin as the hydrophobic structure and the nitrogen heterocyclic ketone as the cationic center, the biaryl compound, the substituted isatin and the nitrogen heterocyclic ketone are subjected to continuous condensation reaction under the catalytic action of an acid so as to form a substituted isatin aromatic copolymer.

[0093] 1.1) 7.83 g of p-terphenyl, 5.6 g of 5-fluoroindigo red and 3.85 g of 1-methyl-4-piperidone were dissolved in 21.7 mL of dichloromethane to obtain a reaction solution.

[0094] 1.2) The reaction flask containing the reaction solution was immersed in an ice-water bath, 3.0 mL of trifluoroacetic acid was added at 0°C, and 24.4 mL of trifluoromethanesulfonic acid was added dropwise. After stirring at this temperature for 2 h, a dark brown viscous solution was obtained.

[0095] 1.3) Pour the viscous solution into 250 mL of potassium carbonate solution, soak for 18 h, break up the precipitate, filter and obtain a semi-solid polymer.

[0096] 1.4) The semi-solid polymer was immersed in potassium carbonate solution again and stirred at 45°C for 18 hours to obtain a brown-grey solid polymer.

[0097] 1.5) The polymer was washed with deionized water for several times until it became neutral, and dried at 80° C. for 24 h to obtain a substituted isatin aromatic copolymer.

[0098] The substituted isatin aromatic copolymers prepared in Examples 1 to 5 were used to prepare polymer anion exchange membranes.

[0099] Application Example 1

[0100] This application example provides a method for preparing a polymer anion exchange membrane.

[0101] Step 1, dissolving the substituted indigo carmine aromatic copolymer in a solvent to obtain a first mixed solution; in a dark and closed environment, adding methyl iodide to the first mixed solution, stirring the reaction and then filtering under reduced pressure to obtain a filtrate, adding the filtrate to a precipitant, and reacting the nitrogen heterocyclic group in the indigo carmine aromatic copolymer with methyl iodide to form a quaternary ammonium polymer to obtain a quaternary ammonium polymer.

[0102] 1.1) 1.0 g of AFuI-10a prepared in Example 1 was dissolved in 20 mL of dimethyl sulfoxide to obtain a first mixed solution.

[0103] 1.2) Add 1 ml of iodomethane to the first mixed solution, heat the mixture to 40° C. in a heating mantle, stir the mixture in a dark, sealed environment for 24 h, and filter the mixture under reduced pressure to obtain a filtrate.

[0104] 1.3) Slowly add the filtrate into ether to obtain a polymer, wash the polymer with ethanol or deionized water, filter, and then dry in a drying oven at 80°C for 24 hours to obtain a quaternized polymer. The preparation reaction route is shown in Reaction Formula 4:

[0105]

[0106] The H NMR spectrum of QAFuI-10a is as follows Figure 1 As shown, the data of nuclear magnetic hydrogen spectrum are as follows: 1 HNMR (400 MHz, DMSO-d6, ppm) δH=10.79, 7.71-6.89, 3.34, 3.26, 3.10, 2.89, 2.50, 2.00, indicating that the present invention successfully synthesized the quaternary ammonium polymer.

[0107] Step 2: using a quaternary ammonium polymer as a raw material, dissolving the quaternary ammonium polymer in a solvent to obtain a second mixed solution, casting the second mixed solution to obtain a substrate membrane, and exchanging hydroxide ions on the substrate membrane to obtain a polymer anion exchange membrane.

[0108] 2.1) Weigh 0.4 g of quaternary ammonium polymer and dissolve it in 20 mL of dimethyl sulfoxide, stirring to dissolve it, to obtain a second mixed solution.

[0109] 2.2) Cast the second mixed solution on clean glass and dry it at 80° C. to obtain a substrate film.

[0110] 2.3) The substrate membrane is peeled off from the glass and immersed in a 1 mol / L NaOH solution for hydroxide ion exchange to obtain a polymer anion exchange membrane with hydroxide as an anion, which is recorded as QAFuI-10a exchange membrane. The preparation reaction route is shown in Reaction Formula 5:

[0111]

[0112] Application Example 2

[0113] This application example provides a method for preparing a polymer anion exchange membrane.

[0114] Step 1, dissolving the substituted indigo carmine aromatic copolymer in a solvent to obtain a first mixed solution; in a dark and closed environment, adding methyl iodide to the first mixed solution, stirring the reaction and then filtering under reduced pressure to obtain a filtrate, adding the filtrate to a precipitant, and reacting the nitrogen heterocyclic group in the indigo carmine aromatic copolymer with methyl iodide to form a quaternary ammonium polymer to obtain a quaternary ammonium polymer.

[0115] 1.1) 1.0 g of the substituted isatin aromatic copolymer prepared in Example 2 was dissolved in 1 mL of dimethyl sulfoxide to obtain a first mixed solution.

[0116] 1.2) Add 1 ml of iodomethane to the first mixed solution, heat to 40° C. in a heating mantle, stir in a dark and sealed environment for 24 h, and filter under reduced pressure to obtain a filtrate.

[0117] 1.3) Slowly add the filtrate into ether to obtain a polymer, wash the polymer with ethanol or deionized water, filter, and then dry in a drying oven at 80°C for 24 hours to obtain a quaternized polymer. The preparation reaction route is shown in Reaction Formula 6:

[0118]

[0119] The H NMR spectrum of QAFuI-7b is as follows Figure 2 As shown, the data of nuclear magnetic hydrogen spectrum are as follows: 1 HNMR (400 MHz, DMSO-d6, ppm) δH=11.0, 7.71-7.00, 3.60, 3.34, 3.10, 2.89, 2.50, 2.00, indicating that the present invention successfully synthesized the quaternary ammonium polymer.

[0120] Step 2, preparation of polymer anion exchange membrane: using quaternary ammonium polymer as raw material, dissolving the quaternary ammonium polymer in a solvent to obtain a second mixed solution, casting the second mixed solution to obtain a substrate membrane, and exchanging hydroxide ions on the substrate membrane to obtain a polymer anion exchange membrane.

[0121] 2.1) Weigh 0.4 g of quaternary ammonium polymer and dissolve it in 20 mL of dimethyl sulfoxide, stirring to dissolve it, to obtain a second mixed solution.

[0122] 2.2) Cast the second mixed solution on clean glass and dry it at 80° C. to obtain a substrate film.

[0123] 2.3) The substrate membrane is peeled off from the glass and immersed in a 1 mol / L NaOH solution for ion exchange to obtain a polymer anion exchange membrane with hydroxide as an anion, which is referred to as QAFuI-7b exchange membrane. The preparation reaction route is shown in Reaction Scheme 7:

[0124]

[0125] Application Example 3

[0126] This application example provides a method for preparing a polymer anion exchange membrane.

[0127] Step 1, dissolving the substituted indigo carmine aromatic copolymer in a solvent to obtain a first mixed solution; in a dark and closed environment, adding methyl iodide to the first mixed solution, stirring the reaction and then filtering under reduced pressure to obtain a filtrate, adding the filtrate to a precipitant, and reacting the nitrogen heterocyclic group in the indigo carmine aromatic copolymer with methyl iodide to form a quaternary ammonium polymer to obtain a quaternary ammonium polymer.

[0128] 1.1) 1.0 g of the substituted isatin aromatic copolymer prepared in Example 3 was dissolved in 20 mL of dimethyl sulfoxide to obtain a first mixed solution.

[0129] 1.2) Add 1 ml of iodomethane to the first mixed solution, heat the mixture to 40° C. in a heating mantle, stir the mixture in a dark, sealed environment for 24 h, and filter the mixture under reduced pressure to obtain a filtrate.

[0130] 1.3) Slowly add the filtrate into ether to obtain a polymer, wash the polymer with ethanol or deionized water, filter, and then dry in a drying oven at 80°C for 24 hours to obtain a quaternized polymer. The preparation reaction route is shown in Reaction Formula 8:

[0131]

[0132] The H NMR spectrum of QAFuI-10c is as follows Figure 3 As shown, the data of nuclear magnetic hydrogen spectrum are as follows: 1 HNMR (400 MHz, DMSO-d6, ppm) δH=10.79, 7.73-6.90, 3.65, 3.34, 3.26, 3.10, 2.89, 2.50, 2.00, indicating that the present invention successfully synthesized the quaternary ammonium polymer.

[0133] Step 2: using a quaternary ammonium polymer as a raw material, dissolving the quaternary ammonium polymer in a solvent to obtain a second mixed solution, casting the second mixed solution to obtain a substrate membrane, and exchanging hydroxide ions on the substrate membrane to obtain a polymer anion exchange membrane.

[0134] 2.1) Weigh 0.4 g of quaternary ammonium polymer and dissolve it in 20 mL of dimethyl sulfoxide, stirring to dissolve it, to obtain a second mixed solution.

[0135] 2.2) Cast the second mixed solution on a clean glass and dry it at 80° C. to obtain a substrate film.

[0136] 2.3) The substrate membrane is peeled off and immersed in a 1 mol / L NaOH solution for ion exchange to obtain a QAFuI-10c exchange membrane whose anion is hydroxide. The preparation reaction route is shown in Reaction Formula 9:

[0137]

[0138] Application Example 4

[0139] This application example provides a method for preparing a polymer anion exchange membrane.

[0140] Step 1, dissolving the substituted indigo carmine aromatic copolymer in a solvent to obtain a first mixed solution; in a dark and closed environment, adding methyl iodide to the first mixed solution, stirring the reaction and then filtering under reduced pressure to obtain a filtrate, adding the filtrate to a precipitant, and reacting the nitrogen heterocyclic group in the indigo carmine aromatic copolymer with methyl iodide to form a quaternary ammonium polymer to obtain a quaternary ammonium polymer.

[0141] 1.1) 1.0 g of the substituted isatin aromatic copolymer prepared in Example 4 was dissolved in 5 mL of N,N-dimethylformamide to obtain a first mixed solution.

[0142] 1.2) Add 3 ml of iodomethane to the first mixed solution, heat to 45° C. in a heating mantle, stir in a dark and sealed environment for 30 h, and filter under reduced pressure to obtain a filtrate.

[0143] 1.3) Slowly add the filtrate into ether to obtain a polymer, wash the polymer with ethanol or deionized water, filter, and then dry in a drying oven at 80° C. for 24 hours to obtain a quaternized polymer.

[0144] Step 2: Using a quaternary ammonium polymer as a raw material, dissolving the quaternary ammonium polymer in N,N-dimethylformamide to obtain a second mixed solution, casting the second mixed solution to obtain a substrate membrane, and exchanging hydroxide ions on the substrate membrane to obtain a polymer anion exchange membrane.

[0145] 2.1) Weigh 0.4 g of the quaternary ammonium polymer and dissolve it in 25 mL of N,N-dimethylformamide, stirring to dissolve it, to obtain a second mixed solution.

[0146] 2.2) Cast the second mixed solution on a clean glass and dry it at 80° C. to obtain a substrate film.

[0147] 2.3) The substrate membrane was peeled off from the glass and immersed in a 1 mol / L NaOH solution for ion exchange to obtain a polymer anion exchange membrane whose anions are hydroxide.

[0148] Application Example 5

[0149] This application example provides a method for preparing a polymer anion exchange membrane.

[0150] Step 1, dissolving the substituted indigo carmine aromatic copolymer in a solvent to obtain a first mixed solution; in a dark and closed environment, adding methyl iodide to the first mixed solution, stirring the reaction and then filtering under reduced pressure to obtain a filtrate, adding the filtrate to a precipitant, and reacting the nitrogen heterocyclic group in the indigo carmine aromatic copolymer with methyl iodide to form a quaternary ammonium polymer to obtain a quaternary ammonium polymer.

[0151] 1.1) 1.0 g of the substituted isatin aromatic copolymer prepared in Example 5 was dissolved in 30 mL of N,N-dimethylformamide to obtain a first mixed solution.

[0152] 1.2) Add 5 ml of iodomethane to the first mixed solution, heat to 50° C. in a heating mantle, stir in a dark and sealed environment for 36 h, and filter under reduced pressure to obtain a filtrate.

[0153] 1.3) Slowly add the filtrate into ether to obtain a polymer, wash the polymer with ethanol or deionized water, filter, and then dry in a drying oven at 80° C. for 24 hours to obtain a quaternized polymer.

[0154] Step 2: Using a quaternary ammonium polymer as a raw material, dissolving the quaternary ammonium polymer in N,N-dimethylformamide to obtain a second mixed solution, casting the second mixed solution to obtain a substrate membrane, exchanging hydroxide ions on the substrate membrane to obtain a polymer anion exchange membrane whose anions are hydroxide.

[0155] 2.1) Weigh 0.4 g of the quaternary ammonium polymer and dissolve it in 30 mL of N,N-dimethylformamide, stirring to dissolve it, to obtain a second mixed solution.

[0156] 2.2) Cast the second mixed solution on clean glass and dry it at 80° C. to obtain a substrate film.

[0157] 2.3) The substrate membrane was peeled off from the glass and immersed in a 1 mol / L NaOH solution for ion exchange to obtain a polymer anion exchange membrane whose anions are hydroxide.

[0158] Experimental test:

[0159] Take Examples 1 to 3 as examples to carry out corresponding tests.

[0160] 1. Nuclear Magnetic Resonance Hydrogen Spectrum Test

[0161] The substituted isatin aromatic copolymers prepared in Examples 1 to 3 were subjected to H NMR testing. The results are as follows: Figure 1 to Figure 3 shown.

[0162] Figure 1 This is the hydrogen nuclear magnetic resonance spectrum of QAFuI-10a prepared in Example 1.

[0163] Figure 2 This is the hydrogen nuclear magnetic resonance spectrum of QAFuI-7b prepared in Example 2.

[0164] Figure 3 This is the hydrogen nuclear magnetic resonance spectrum of QAFuI-10c prepared in Example 3.

[0165] 2. Mechanical properties test

[0166] The polymer anion exchange membranes prepared in Application Example 1 and Application Example 2 were stretched at a speed of 50 mm / min on a tensile testing instrument until the membranes broke, and the mechanical properties were tested. The results are as follows: Figure 4 and Figure 5 shown.

[0167] Figure 4 The mechanical strength of the QAFuI-10a exchange membrane prepared in Example 2 in a wet state. Figure 5 As shown, under wet conditions, the tensile strength of the QAFuI-10a exchange membrane is 27 MPa, and the elongation at break is 70%, indicating that the QAFuI-10a exchange membrane has very excellent tensile strength and elongation at break, and can effectively increase the pressure resistance of the device and increase the life of the device when used.

[0168] Figure 5 The mechanical strength of the QAFuI-7b exchange membrane prepared in Example 1 in a wet state. Figure 5 It can be seen that the tensile strength of QAFuI-7b exchange membrane in wet state can reach 28MPa, and the elongation at break is 57%, which indicates that QAFuI-7b exchange membrane has excellent tensile strength.

[0169] 3. Conductivity test

[0170] The conductivity test of the polymer anion exchange membrane prepared in Application Example 1 and Application Example 2 was conducted using an electrochemical high-frequency AC impedance tester, using a four-electrode method with a frequency range of 1 Hz to 10000 Hz. The QAFuI-7b exchange membrane and QAFuI-10a exchange membrane were cut into 1 cm × 4 m sizes for testing. The results are as follows: Figure 6 and Figure 7 shown.

[0171] Figure 6 is the hydroxyl ion conductivity of QAFuI-10a exchange membrane at different temperatures. Figure 6 As shown in the figure, the conductivity of QAFuI-10a exchange membrane reaches 80mS / cm at 40℃, and QAFuI-10a exchange membrane can achieve efficient hydroxide transmission rate. This shows that the introduction of fluorinated substituents can effectively improve the ion transmission performance of anion exchange membrane without affecting other properties of the material.

[0172] Figure 7is the hydroxide ion conductivity of QAFuI-7b exchange membrane at different temperatures. Since the substituted indigo carmine in Example 1 is a monofluorinated substituted indigo carmine, the difluorinated substituted indigo carmine increases the hydrophobicity of the indigo carmine fragment compared to the monofluorinated substituted indigo carmine, which plays a vital role in the microscopic phase separation of the anion exchange membrane. Compared with Example 1, the ionic conductivity of the QAFuI-7b exchange membrane at 80°C exceeds 160mS / cm. The introduction of fluorinated substituents can effectively improve the ion transport performance of the anion exchange membrane without affecting other properties of the material. This type of anion exchange membrane with high ion transport performance is applied to alkaline membrane water electrolysis devices, showing very excellent performance.

[0173] 4. Swelling rate test

[0174] Figure 8 The changes of water content swelling rate of QAFuI-10a exchange membrane at different temperatures. Figure 8 As shown, at 80°C, the QAFuI-10a exchange membrane has a very low swelling rate of only 9.6%. This low swelling has great advantages for anion exchange membranes in water electrolysis, fuel cells, and electrochemical carbon dioxide reduction devices, and can further reduce the difficulty of device assembly and improve the structural stability of the device.

[0175] 5. Water electrolysis hydrogen production performance test

[0176] In the water electrolysis hydrogen production electrolyzer, the cathode uses a platinum carbon catalyst, the anode uses a non-precious metal catalyst nickel-cobalt alloy, and a 75μm QAFuI-7b is used as an exchange membrane. A 1M KOH solution is passed through the cathode and anode. The test is carried out at 80°C. The results are as follows Fig. 9 shown.

[0177] Fig. 9 The performance of QAFuI-7b in alkaline anion exchange membrane water electrolysis device. Fig. 9 It can be seen that the QAFuI-7b water electrolysis hydrogen production electrolyzer can achieve a current density of 1080mA / cm 2 @1.8V, and 2200mA / cm 2 @2.0V, indicating that the water electrolysis performance of QAFuI-7b exchange membrane is excellent.

[0178] Therefore, QAFuI-10a has excellent performance in terms of physical strength, anti-swelling and chemical properties, and has great room for development.

[0179] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. If these modifications and variations of the present invention fall within the scope of the equivalent technology of the present invention, the present invention is also intended to include these modifications and variations.

Claims

1. A substituted isatin aromatic copolymer, characterized in that: The chemical structure is shown in formula 1: Wherein, R1, R2, R3 and R4 are independently selected from one of methyl, alkyl, halogenated alkyl, H, F, Cl and Br substituents; R5 is H or a carbon straight chain alkyl with 1 to 12 carbon atoms; Ar is a biaryl compound; and B is an azacyclic ketone.

2. The method for preparing the substituted isatin aromatic copolymer according to claim 1, characterized in that: The following steps are involved: With the aromatic structure of the biaryl compound as the main chain, the substituted isatin as the hydrophobic structure and the nitrogen heterocyclic ketone as the cationic center, the biaryl compound, the substituted isatin and the nitrogen heterocyclic ketone are subjected to continuous condensation reaction under the catalytic action of an acid so as to form a substituted isatin aromatic copolymer.

3. The method for preparing the substituted isatin aromatic copolymer according to claim 2, characterized in that: The following steps are involved: dissolving the biaryl compound, substituted isatin and azacyclic ketone in a solvent in sequence to obtain a reaction solution; In a water bath at 0°C, trifluoroacetic acid was added to the reaction solution, and then trifluoromethanesulfonic acid was added dropwise to obtain a viscous solution; The viscous solution is immersed in a potassium carbonate solution for multiple times, so that the nitrogen protonated by the acid on the nitrogen heterocycle is converted into a non-protonated nitrogen heterocycle through an acid-base reaction, thereby obtaining a solid polymer; The solid polymer is washed and dried to obtain a substituted isatin aromatic copolymer.

4. The method for preparing the substituted isatin aromatic copolymer according to claim 3, characterized in that: The substituted isatin includes one of 5-methylisatin, 7-methylisatin, 5-fluoroisatin, 6-fluoroisatin, 7-fluoroisatin, 5,6-difluoroisatin, 4,6-difluoroisatin, 5,7-difluoroisatin, 6-chloroisatin, 7-chloroisatin and 7-trifluoromethylisatin.

5. The method for preparing the substituted isatin aromatic copolymer according to claim 4, characterized in that: The molar ratio of the total molar number of the substituted isatin and the azacyclic ketone to the biaryl compound is 1 to 2:1; The molar ratio of the substituted isatin to the azacyclic ketone is 1:0.01-99.

6. The method for preparing the substituted isatin aromatic copolymer according to claim 4, characterized in that: The molar ratio of the biaryl compound to trifluoroacetic acid is 1:0.1-2.0; The molar ratio of the biaryl compound to trifluoromethanesulfonic acid is 1:1-50.

7. The method for preparing the substituted isatin aromatic copolymer according to claim 4, characterized in that: The soaking time is 12 hours to 18 hours.

8. A polymer anion exchange membrane, characterized in that: The method is prepared from the substituted isatin aromatic copolymer according to claim 1, comprising the following steps: The substituted isatin aromatic copolymer is dissolved in a first solvent to obtain a first mixed solution; in a dark and closed environment, methyl iodide is added to the first mixed solution, stirred for reaction, and then filtered under reduced pressure to obtain a filtrate, the filtrate is added to a precipitant, and the nitrogen heterocyclic group in the isatin aromatic copolymer undergoes a methylation reaction with methyl iodide to form a quaternized polymer, thereby obtaining a quaternized polymer; The quaternary ammonium polymer is used as a raw material, the quaternary ammonium polymer is dissolved in a second solvent to obtain a second mixed solution, the second mixed solution is cast to obtain a base film, and the base film is subjected to hydroxide ion exchange to obtain a polymer anion exchange membrane.

9. The polymer anion exchange membrane according to claim 8, characterized in that The usage ratio of the substituted isatin aromatic copolymer to methyl iodide is 1.0 g: 1 mL to 5 mL.

10. The polymer anion exchange membrane according to claim 8, characterized in that The first solvent and the second solvent are both one of dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide and N-methylpyrrolidone.

Citation Information

Patent Citations

  • Isatin aromatic hydrocarbon copolymer, preparation method and application thereof

    CN110903449A

  • Preparation method of fluorine-containing polyaryl isatin anion exchange membrane

    CN117343368A

  • Sulfonated poly(isatin-ethersulfone), method for preparing the same and polymer membrane composition for fuel cell using the same

    KR1020160081117A

Cited By

  • Branched substituted isatin aromatic hydrocarbon copolymer, anion exchange membrane and preparation method of anion exchange membrane

    CN121248869A